2016
DOI: 10.3892/ijo.2016.3729
|View full text |Cite
|
Sign up to set email alerts
|

B-cell CLL/lymphoma 3 promotes glioma cell proliferation and inhibits apoptosis through the oncogenic STAT3 pathway

Abstract: Aberrant expression of oncogenes and/or tumor suppressors play fundamental roles in the pathogenesis of glioma. B-cell CLL/lymphoma 3 (BCL3) was previously found to be a putative proto-oncogene in human cancers and the decoy receptor DcR1 is induced in a p50/Bcl3-dependent manner and attenuates the efficacy of temozolomide in glioblastoma cells. However, its expression status, clinical significance and biological functions in glioma remain largely unknown. In the present study, the levels of BCL3 were overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In addition to these proliferation findings, we found that minimally injured ONHs showed an upregulation of several interleukin-6 type cytokines ( Il6, Lif, Clcfl ) and Socs3 , the feedback inhibitor of Stat3 phosphorylation (pStat3), suggesting an early activation of the Janus kinase and signal transducer and activator of transcription (Jak-Stat) pathway 18,19. Jak-Stat pathway activation has been shown to regulate glial cell proliferation, as well as astrocytic differentiation, and this pathway may play an important role in the glial responses we have observed in pressure-induced injury 17,18,2125…”
mentioning
confidence: 88%
“…In addition to these proliferation findings, we found that minimally injured ONHs showed an upregulation of several interleukin-6 type cytokines ( Il6, Lif, Clcfl ) and Socs3 , the feedback inhibitor of Stat3 phosphorylation (pStat3), suggesting an early activation of the Janus kinase and signal transducer and activator of transcription (Jak-Stat) pathway 18,19. Jak-Stat pathway activation has been shown to regulate glial cell proliferation, as well as astrocytic differentiation, and this pathway may play an important role in the glial responses we have observed in pressure-induced injury 17,18,2125…”
mentioning
confidence: 88%
“…Although many other proteins have been found to contribute to GBM tumor growth, for this review, we will focus on targets that have been discovered through proteomic approaches and TCGA data mining. Some examples of proteins overexpressed in GBM that may represent novel drug targets that were not discovered via proteomic approaches include heat-shock protein 47 ( Jiang et al, 2017b ), cathepsin L ( Xiong et al, 2017 ), glycoprotein nonmetastatic melanoma protein B ( Ono et al, 2016 ), transcription factor 12 ( Godoy et al, 2016 ), targeting protein for Xenopus kinesin-like protein 2 ( Gu et al, 2016 ), and B-cell CLL/lymphoma 3 (BCL3) ( Wu et al, 2016 ). Due to the characteristic intratumoral heterogeneity of GBM, it is likely that a single target approach will not be effective, and appropriate drug combinations will be necessary.…”
Section: Characteristics Of Protein Expression In Glioblastomamentioning
confidence: 99%
“…15 In glioblastoma cells, Bcl-3 significantly facilitated proliferation by stabilizing the expression of STAT3, p-STAT3, and STAT3 signaling target genes, including Bcl-2, MCL-1, and cyclin D1. 16 Recently, the function of Bcl-3 in CRC has been reported by various research groups. First, Bcl-3 was found to promote CRC cell growth by stabilizing the c-Myc protein level and regulating ERK signaling.…”
Section: Introductionmentioning
confidence: 99%